Answer:
Step-by-step explanation:
6x^2+4x-42
2(3x^2+2x-21)=0
3x^2+2x-21=0
3x^2+(9-7)x-21=0
3x^2+9x-7x-21=0
3x(X+3)-7(X+3)=0
(3X-7)(X+3)=0
So Answer is (3x-7)(X+3)
Do 4+3+5 which = 12
then do 48 divided by 12 which is 4
Now 4 x 4 = 16
3 x 4 = 12
5 x 4 = 20
16 + 12 + 20 = 48 so its divided as 16:12:20
Answer:
Can you explain clearer?
Step-by-step explanation:
Answer:
The solution is
Step-by-step explanation:
To solve the differential equation, we will find ![y](https://tex.z-dn.net/?f=y)
From the given equation, y' + 5xey = 0.
That is, ![y' + 5xe^{y} = 0](https://tex.z-dn.net/?f=y%27%20%2B%205xe%5E%7By%7D%20%3D%200)
This can be written as
![\frac{dy}{dx} + 5xe^{y} = 0](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdx%7D%20%2B%205xe%5E%7By%7D%20%3D%200)
Then,
![\frac{dy}{dx} = - 5xe^{y}](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdx%7D%20%3D%20-%205xe%5E%7By%7D)
![\frac{dy}{e^{y}} = - 5x dx](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Be%5E%7By%7D%7D%20%20%20%3D%20-%205x%20dx)
Then, we integrate both sides
![\int {\frac{dy}{e^{y}}} =\int {- 5x dx}](https://tex.z-dn.net/?f=%5Cint%20%7B%5Cfrac%7Bdy%7D%7Be%5E%7By%7D%7D%7D%20%20%3D%5Cint%20%7B-%205x%20dx%7D)
![\int {e^{-y}dy }} =\int {- 5x dx}](https://tex.z-dn.net/?f=%5Cint%20%7Be%5E%7B-y%7Ddy%20%7D%7D%20%20%3D%5Cint%20%7B-%205x%20dx%7D)
Then,
![-e^{-y} = -\frac{5}{2}x^{2} + C](https://tex.z-dn.net/?f=-e%5E%7B-y%7D%20%3D%20-%5Cfrac%7B5%7D%7B2%7Dx%5E%7B2%7D%20%2B%20C)
![e^{-y} = \frac{5}{2}x^{2} + C](https://tex.z-dn.net/?f=e%5E%7B-y%7D%20%3D%20%5Cfrac%7B5%7D%7B2%7Dx%5E%7B2%7D%20%2B%20C)
Then,
![ln(e^{-y}) = ln(\frac{5}{2}x^{2} + C)](https://tex.z-dn.net/?f=ln%28e%5E%7B-y%7D%29%20%3D%20ln%28%5Cfrac%7B5%7D%7B2%7Dx%5E%7B2%7D%20%2B%20C%29)
Then,
![-y = ln(\frac{5}{2}x^{2} + C)](https://tex.z-dn.net/?f=-y%20%3D%20ln%28%5Cfrac%7B5%7D%7B2%7Dx%5E%7B2%7D%20%2B%20C%29)
Hence,
Answer:
248.40
Step-by-step explanation:
plz make me branliest and like